Temporal variation in black-caiman-nest predation in varzea of central Brazilian amazonia. - Kelly Torralvo; Robinson Botero-Arias; William E Magnusson (PLoS ONE)
On the Amazon floodplain, the main predators of black caiman (Melanosuchus niger) eggs are jaguars (Panthera onca), tegu lizards (Tupinambis teguixim), capuchin monkeys (Sapajus macrocephalus) and humans (Homo sapiens). In this study, we investigated the relationship between predator attacks on nests and incubation period, and evaluated the influence of initial predation on subsequent predation in the Mamirauá Sustainable Development Reserve. We also evaluated the influence of presence of females near the nests and manipulation of nests on the occurrence of attacks. We compared results from data obtained with camera traps and vestiges left by predators on estimates of rates of predation by different predators. Egg predation was recorded in 32% of the 658 black caiman nests monitored during two years. Our results suggest that the probability of predation on black caiman eggs is relatively constant throughout the incubation period and that predation on eggs was lower when adults, presumably females, were present. Careful opening of nests and handling of eggs did not increase the number of attacks on black caiman nests. Nest opening by a predator appeared to increase the chances of a subsequent attack because most of the attacks on nests occurred soon after a predator first opened the nest. However, attacks by another species of predator do not appear to be necessary to initiate attacks by any other species of predator. Results based on camera traps and vestiges differed, but use of vestiges was adequate for identifying the principal predators on eggs in black caiman nests and, in many circumstances, the vestiges may be better for estimating predation by humans. In this study, opening nests and handling eggs did not increase the number of attacks on black caiman nests.